An effective strategy for in situ start-up of mainstream anammox process treating domestic sewage. (November 2021) - Zhang, Jianhua; Miao, Yuanyuan; Sun, Yawen; Zhang, Qiong; Dai, Jiatong; Peng, Yongzhen
Graphical abstract: Highlights: Mainstream anammox process was started up in situ via simple operation strategy. Desirable NRE of about 86% was obtained despite the fluctuation in sewage quality. Validity of the start-up strategy was verified with three kinds of seed sludge. Biofilm and anaerobic/aerobic/anoxic mode favored enrichment of anammox bacteria. Seed sludge with high AOB activity promoted the in situ start-up of anammox process. Abstract: The feasibility of in situ start-up of mainstream anammox process was investigated in three parallel sequencing batch biofilm reactors (SBBRs) inoculated with nitrification sludge, partial nitrification sludge, and denitrifying phosphorus removal sludge, respectively. The SBBRs were operated under alternate anaerobic/aerobic/anoxic pattern at ambient temperature (16.5–26.8 °C). The influent organic and nitrogen loading rates were increased stepwise. Anammox bacteria grew exponentially with relative abundance and overall bacterial activity increasing from 0 to 0.004% to 0.29–0.40% and 'not detected' to 6–7 mg N/L/h, respectively. Desirable nitrogen removal efficiency of about 86% was obtained in 3–4 months for the influent nitrogen of 40.5–73.6 mg N/L. Anammox was the primary nitrogen transformation pathway. For the anammox bacterial enrichment, biofilm, alternate anaerobic/aerobic/anoxic pattern, and limited aeration played important roles. Seed sludge with high ammonium oxidizing bacterial activity further promoted the start-up of anammox process. The in situ start-up strategy could promote the full-scale application of mainstream anammox.